Pengaruh Model Pembelajaran Game Based Learning Berbantuan Quizizz terhadap Kemampuan Pemecahan Masalah Matematis Siswa SMK - Ina Ramadina; Hepsi Nindiasari (Departement of Mathematics Education, 2025)
This research aims to determine the effect of the Game Based Learning learning model assisted by Quizizz on vocational school students' mathematical problem solving abilities. The population in this study was all students of Bismillah Vocational School and the sample was students of class X TJKT 1 as the control class and class X DKV as the experimental class. The sampling technique is to use the cluster random sampling technique. This research uses quantitative research methods, the research instruments used are pretest and posttest. This type of research is quasi-experimental research. Based on the results of this research, Game Based Learning influences students' mathematical problem solving abilities. The results of hypothesis testing obtained a value of ????ℎ????????????????????>????????????????????????, namely 12.85 > 2.045, indicating that there is a significant influence on Game Based Learning assisted by Quizizz on the mathematical problem solving abilities of vocational school students.